När popen kom - Ronström, Owe (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2006)
As a part of an intensive production of different pasts, there is today a growing interest in the 1960’s. This article examines how pop music hit Visby, a small town in Sweden, in the early 60’s. The main questions adressed are about the prerequisites of aesthetic change, and about how the 60’s is remembered and represented in pictures, records and narratives today. In Visby, as in most parts of Sweden, pop music represents an aesthetic revolution, where old European popular music forms are replaced by new afro-american styles. The new musical behaviour became associated with urbanity, modernity, rebellion and youth, and coincided with a fast urbanisation and modernisation of Sweden. In the peripheral small town Visby, pop music opened a new window to a bigger world, which brought new youth closer to centers such as Stockholm, Berlin and London. In the narratives told today the early 60’s is produced as a positive, innocent period, in strong contrast to present times, which leads to the question of when the 60’s actually happened, then or now?